IMPACT OF PERCEIVED ORGANIZATIONAL SUPPORT AND WORKPLACE SPIRITUALITY ON THE RELATIONSHIP BETWEEN ORGANIZATIONAL PERFORMANCE AND WORKPLACE INNOVATION A STUDY OF PUBLIC SECTOR ORGANIZATIONS OF PAKISTAN - Ali, Nasir; Ali, Dr.Amna; Khan, Azhar; Afzal, Ismael (The journal of contemporary issues in business and government, 2021)
The study aims to evaluate the impact of workplace spirituality and perceived organizational support on the relationship between organizational performance and workplace innovation in public sector organizations of Pakistan. For the collection of data and its subsequent analysis, the study has selected quantitative methodology and deductive reasoning with a positivist approach. However, data was collected from 2500 participants through stratified sampling, where the entire public sector of Pakistan was divided into five manageable groups or stratum that include organizations from the banking sector, establishment division, universities, manufacturing and trading sector and healthcare sector of the country. Furthermore, a total of 25 organizations were selected, i.e., five organizations from each sector and each capital city of the four provinces and Islamabad. Data analysis tool STATA was used for testing the responses collected from the participants, and analysis like SEM, regression, correlation, descriptive statistics and Sobel test for mediation was performed. The findings of the study suggest that there is a notable positive relationship between all the independent, dependent and mediating variables of the study. It is also found that perceived organizational support and workplace spirituality have a positive mediating role in the relationship between organizational performance and workplace innovation. Furthermore, certain limitations of the study are also identified, which can be overcome in future studies through a selection of larger sample size and adoption of a mixed method approach for data collection and analysis.